Childhood Maltreatment Was Correlated With the Decreased Cortical Function in Depressed Patients Under Social Stress in a Working Memory Task: A Pilot Study - Ma, Mengying; Zhang, Xiao; Zhang, Yuyanan; Su, Yi; Yan, Hao; Tan, Haoyang; Zhang, Dai; Yue, Weihua (Frontiers in Psychiatry, 2021)
Background: Major depressive disorder (MDD) is a common psychiatric disorder associated with working memory (WM) impairment and complex heterogeneities. Neuroimaging studies showed divergent results of the WM process in MDD patients. Stress could both affect the occurrence and development of depression, in which childhood maltreatment play an important role. Methods: Thirty-seven MDD patients with less age heterogeneity (19~36 years) and 54 healthy control subjects were enrolled and completed a WM functional magnetic resonance imaging task with maintenance and manipulation conditions under stress and non-stress settings. We collected demographical and clinical data, using 17-item Hamilton Depression Scale (HAMD-17) and Childhood Trauma Questionnaire (CTQ) in MDD patients. In the WM task, we analyzed the main diagnosis effect, and explored the correlation of impaired brain regions in MDD patients with CTQ and HAMD-17. Results: No group differences were found in the accuracy rate and reaction time between two groups. MDD patients had lower brain activation in following regions (PFWE < 0.05). Left fusiform gyrus activated less in all conditions. Right supplementary motor area (SMA) showed decreased activation under non-stress. Anterior prefrontal cortex (APFC) showed reduced activation during manipulation under stress, with the beta estimate of the peak group difference negatively correlated with childhood sex abuse (PBonferroni < 0.05). Conclusions: MDD patients had reduced brain activation, which may affect emotional stimuli processing function, executive function, and cognitive control function. Childhood trauma may affect brain function in MDD.